IMPLEMENTASI METODE ROLE PLAYING DALAM PERENCANAAN PEMBELAJARAN DI SEKOLAH DASAR - Herlina, Bella; Khoiriyah, Ismatul (Primer Edukasi Journal, 2026)
Learning planning is an important stage that teachers must carry out before implementing the learning process in the classroom. Good planning will determine the success of achieving learning objectives. One important aspect of learning planning is the selection of learning methods that are appropriate to the characteristics of elementary school students. The Role Playing method is one of the learning methods that is considered capable of creating an active, fun, and meaningful learning atmosphere for students. This scientific article aims to examine in depth the implementation of the Role Playing method in learning planning in elementary schools and its implications for the learning process and outcomes. The research method used is library research with a descriptive qualitative approach. Data were obtained from scientific journals and books relevant to the research topic, especially journals discussing the application of the Role Playing method in elementary schools. The results of the study indicate that the Role Playing method has positive implications in learning planning, especially in increasing student activeness, understanding of material, social skills, and learning interest. Therefore, the Role Playing method can be used as an alternative learning method that needs to be carefully planned by elementary school teachers. Keywords: Learning planning, learning methods, role playing, elementary school